OPTIMALISASI PENDIDIKAN AKHLAK BERBASIS TADZKIYATUN NAFS - Eka Nurul Safitri; Baharudin Baharudin; Beti Susilawati; Uswatun Hasanah; Waluyo Erry Wahyudi (Program Studi Pendidikan Agama Islam STIT al Urwatul Wutsqo Bulurejo Jombang, 2025)
Moral education at MTs Nurul Islam plays a significant role in shaping students' character through the approach of Tazkiyatun Nafs. This research aims to optimize moral education by focusing on three main aspects: implementation, supporting and inhibiting factors, and the outcomes of the learning process. This study uses a phenomenological approach and a qualitative research methodology. Interviews, observations, and documentation were used to gather data. The findings demonstrate that moral education is conducted in an organized way, where teachers utilize various interactive teaching methods to maximize the moral education process. This study seeks to develop a moral education model based on Tazkiyatun Nafs at MTs Nurul Islam. This approach focuses on purification of the soul and moral enhancement through the development of self-awareness, emotional control, and the formation of positive character. Supporting factors include student motivation and adequate facilities, while inhibiting factors involve students’ difficulties in understanding the material. Overall, moral education based on Tazkiyatun Nafs at MTs Nurul Islam has been able to produce positive changes in students' behavior, making them more aware of moral actions and contributing to society. This research recommends improving teaching methods and providing environmental support to further optimize the moral education process in the madrasah.